N-point tree-level scattering amplitude in the new Berkovits' string - Gomez, Humberto [UNESP]; Yuan, Ellis Ye (Springer, 2014)
We give a proof that the pure spinor superstring theory in a novel infinite tension limit, as was discussed recently by Berkovits, reproduces the tree-level scattering amplitudes of the ten-dimensional = 1 super Yang-Mills in its heterotic version and type II supergravity in its type II version. The Yang-Mills case agrees with the result obtained by Mafra, Schlotterer, Stieberger and Tsimpis.
Keywords: Scattering Amplitudes; Supersymmetric gauge theory